Population of bacteria from soil in Tudu-Aog village, Passi district, Bolaang Mongondow, North Sulawesi - SRI PURWANINGSIH; RIANI HARDININGSIH; WARDAH WARDAH; AGUS SUJADI (Society for Indonesian Biodiversity, 2004)
An experiment was conducted in order to know the population of bacteria from soil in Tudu-Aog village, Passi district, Bolaang Mongondow, North Sulawesi, the purpose of the research was to study the population of bacteria from soil. Fourthy six soil samples were taken from two location, namelyTudu-Aog village and Bugis mountain. Isolation was done by dilution methods on YEMA medium (for Rhizobium bacteria), Winogradsky’s (for Azotobacter bacteria), Pycosvkaya (for Phosphat Solubilizing Bacteria), and selective Difco Pseudomonas (for Pseudomonas bacteria). Incubation at room temperature (27-280C) until 15 days, and the enumeration with plate count method. The highest enumeration of Rhizobium bacteria with plant rhizosphere of Alocasia esculenta (27x105 CFU/g soil), Theobroma cacao (29x105 CFU/g soil),and Euphorbia paniculata (26x105 CFU/g soil), Azotobacter bacteria with plant rhizosphere of Lycopersicum esculantum (38x105 CFU/g soil), Eugenia aromaticum (43x105 CFU/g soil), Andropogon sp. (34x105 CFU/g soil), Phosphat Solubilizing bacteria with plant rhizosphere of Sechium edule (27x105 CFU/g soil), Cinnamomum sp. (48x105 CFU/g soil), Cyathea sp. (72x105CFU/g soil), and Pseudomonas bacteria with plant rhizosphere of Oryza sativa (18x105 CFU/g soil), Vanilla sp. (12x105CFU/g soil), dan Saurauia sp.(19x105 CFU/g soil). 2004 Jurusan Biologi FMIPA UNS SurakartaKey words: population, soil, bacteria.